PREPARATION AND CHARACTERIZATION OF POLYMER CONCRETE USING PUMICE AGGREGATE AND COFFEE HUSK FIBER AS A FILLER - Awan Maghfirah; Eddy Marlianto; Mulkan Iskandar Nasution; Putri Mila Senda Sitorus (Universitas Islam Negeri Sumatera Utara Medan, 2018)
Research has been conducted on the preparation and characterization of polymer concrete with certain compositions of sand, pumice, coffee husk fiber, and epoxy resin to get the best mixing composition. All compositions were processed using a hot press machine at a temperature of 90 °C for 20 minutes. The results showed that polymer concrete with optimum characteristics is produced in the mixing composition of sand, pumice, coffee husk fiber, and epoxy resin of 60:14:6:20 g. In this condition, the density is 1.21 g/cm3, porosity is 8.3%, water absorption is 6.81%, flexural strength is 28.68 MPa, compressive strength is 7.67 MPa, and tensile strength is 3.98 MPa. SEM/EDS analysis shows that the addition of epoxy resin can improve the quality of polymer concrete. Keywords: Coffee husk fiber, epoxy resin, polymer concrete, and pumice.